MRE11 orchestrates porcine oocyte meiotic progression by modulating the spindle assembly checkpoint - Zhang, Dandan; Yang, Zaishan; Zhang, Yongteng; Fang, Fugui; Cao, Hongguo; Li, Yunsheng; Cao, Zubing; Xue, Yanfeng; Zhang, Mianqun (Frontiers in Cell and Developmental Biology, 2025)
IntroductionMre11 is a multisubunit nuclease involved in DNA repair, and its dysfunction often causes DNA damage sensitivity, genomic instability, telomere shortening, and aberrant meiosis. However, the specific roles of Mre11 in porcine oocyte meiosis remain unclear.MethodsIn this study, porcine oocytes were treated with the Mre11-specific inhibitor mirin to investigate the function of Mre11 during meiotic maturation. Meiotic progression, spindle and chromosome structure, spindle migration, cytoplasmic actin polymerization, and DNA damage levels were assessed using immunofluorescence and relevant molecular markers including BubR1 and γH2A.X.ResultsInhibition of Mre11 activity led to failure of first polar body extrusion, with sustained BubR1 presence at kinetochores, indicating activation of the spindle assembly checkpoint (SAC). Mre11-inhibited oocytes showed disrupted spindle and chromosome organization due to decreased microtubule stability. Additionally, spindle migration to the oocyte cortex was impaired, correlating with reduced cytoplasmic actin polymerization. Elevated DNA damage levels were observed in treated oocytes as evidenced by increased γH2A.X staining.DiscussionThese findings demonstrate that Mre11 is essential for porcine oocyte meiotic progression by maintaining normal spindle assembly, actin cytoskeleton dynamics, and SAC activity. DNA damage accumulation following Mre11 inhibition likely contributes to meiotic failure, highlighting its critical role in ensuring oocyte quality.